Mapping of Marine Area Boundary of Central Java Province using Differential GPS Survey Method - Khakhim, Nurul; Dulbahri, Dulbahri; Widartono, Barandi Sapta (Forum Geografi, 2002)
The development of GPS (Global Positioning System) technology which is measuring position by satellite, has taken a great metodology aspect of position on surface of earth. The standard GPS measurement takes an absolute positioning. To develop the accurate abd precision, it is used the differential method. Differential GPS measurement can be much more accurate than standard GPs measurement, wherever the method uses one receiver as base station/ reference and the other receiver as field station in a same time. That could reduce and eliminate drifts and errors. The aim of research is use the differential method of GPS survey to map the ocean boundary of Central Java Province. Physical data which neede are base line and base point. Base line were taken from obsrvation of longtime Landsat TM image band 5th based o opinion that shore line are clear seems and easy to interpreted at 10.00 am according to Landsat satellite reording time and the lowest tide time as base line. Location of lowest tide were selected at conspicuous place, such as cape, dry shore, etc and measured base on the BPN (Badan Pertahanan Nasional) base/ reference point (orde 2 and 3) on the district, with GPS differential metod. Twelve miles distance from base line of ocean bounddary is belong to province and 1/3 of is belong to district. Characteristic of marine landform as cape, bay, estuaria, attended to international rules. Final report of the research were 1) oean boundary map of Center Java Province, 2) the location and base/ reference points (orde 2 and 3) that could be reference as a base point differential method.